Assessment of the Psychological Wellbeing of Elderly Residing at Pooncheri Rural Community Area in Kancheepuram District, Tamilnadu, India (Medico Legal Update, 2020)
A descriptive Study on Assessment of the psychological wellbeing residing in pooncheri rural communityarea in kancheepuram (dist.), Tamil Nadu India. The objectives are to assess psychological wellbeing ofelderly people. To find out the association between levels of psychological wellbeing of elderly people andselected demographic variables of elderly people. The sampling technique was non-probability, purposivesampling technique with 111 samples of elderly people and WHO standardized psychological wellbeing scalewere used to assess psychological wellbeing of elderly. The demographic variables Performa, were used tocollect data. The data collection tools were validated and reliability was established. The data collection forthe main study was done. The collected data was tabulated and analyzed, using descriptive and inferentialstatistics. Majority of elderly 71.2% had adequate, 28.8% had moderate wellbeing, There no poor wellbeing.The psychological wellbeing mean value is57.34.